EFEKTIVITAS PENELITIAN TINDAKAN KELAS (PTK) TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN SAINS DI SMA - Tuti Supriyanti; Rahma Dani (JURNAL FIRNAS, 2026)
Abstract: This study aims to analyze the effectiveness of Classroom Action Research (CAR) in improving students’ learning outcomes in science learning at the senior high school level based on a review of 50 reputable national and international journal articles. The research method used was a literature review with a qualitative descriptive approach. Data were analyzed based on learning problems, CAR cycle design, research subjects, instruments, data analysis techniques, and research results in each cycle. The findings indicate that the systematic implementation of CAR through planning, action, observation, and reflection stages significantly improves students’ learning outcomes, learning activities, and learning mastery in each cycle. Most studies reported a consistent increase in cognitive achievement and conceptual understanding from cycle I to cycle II. Therefore, Classroom Action Research is proven to be an effective and reflective approach to improving the quality of science learning in high schools.